KARAKTERISTIK IBU MEMBERIKAN MAKANAN PENDAMPING ASI (MP-ASI) PADA BAYI USIA 0 – 6 BULAN DI WILAYAH KERJA PUSKESMAS HARAPAN RAYA PEKANBARU TAHUN 2018 - Berliana Irianti; Eka Purnama Sari (STIKes Al-Insyirah Pekanbaru, 2019)
Complementary food breastfeeding are foods that contain nutrients, given to children age 6 – 24 months to fulfill their nutritional needs Complementary food breastfeeding precisely influenced by the behavior of mothers who have babies. But there are still many mothers giving complementary foods breastfeeding for less than 6 months, which can cause a negative impact for health of the baby such as diarrhoea and even death can result in babies. This research aims to know the characteristics of mothers in giving Complementary Food breastfeeding for less than 6 months. This research is quantitative descriptive design with population of mothers that have babies aged 7-12 months amounted to 2,494 people, with 96 samples taken with quota sampling, this research was conducted in the working area of Harapan Raya Health Centre Pekanbaru on March – April 2018, data was collection is done by filling the questionnaire. The research results obtained 91 people (94.79%) respondents aged 20 – 35 years, 56 people (58.33%) respondents primigravida, 76 people (79.18%) respondents have High School, 71 people (73.96%) respondents it does not work , 57 people (59.37%) respondents knowledgeable enough. Based on the results obtained is expected that health worker can increase counselling to mothers about breastfeeding and how to overcome the problems that occur while breastfeeding so giving exclusive breasfeeding can be implemented properly.